Guidance regarding COVID-19 for survivors of childhood, adolescent, and young adult cancer: A statement from the International Late Effects of Childhood Cancer Guideline Harmonization Group - Verbruggen, Lisanne C; Wang, Yuehan; Armenian, Saro H; Ehrhardt, Matthew J; van der Pal, Helena J H; van Dalen, Elvira C; van As, Jorrit W; Bardi, Edit; Baust, Katja; Berger, Claire; Castagnola, Elio; Devine, Katie A; et al. (Pediatric blood & cancer, 2020)
Childhood, adolescent, and young adult (CAYA) cancer survivors may be at risk for a severe course of COVID-19. Little is known about the clinical course of COVID-19 in CAYA cancer survivors, or if additional preventive measures are warranted. We established a working group within the International Late Effects of Childhood Cancer Guideline Harmonization Group (IGHG) to summarize existing evidence and worldwide recommendations regarding evidence about factors/conditions associated with risk for a severe course of COVID-19 in CAYA cancer survivors, and to develop a consensus statement to provide guidance for healthcare practitioners and CAYA cancer survivors regarding COVID-19.
Keywords: Adolescent; Adult; Neoplasms; Male; lidé; pandemie; Humans; late effects of cancer treatment; Child; Coronavirus Infections; COVID-19; Young Adult; Child, Preschool; koronavirové infekce; směrnice pro lékařskou praxi jako téma; přežívající onkologičtí pacienti; Pandemics; Practice Guidelines as Topic; Pneumonia, Viral; mužské pohlaví; nádory; SARS-CoV-2; dospělí; childhood adolescent and young adult (CAYA) cancer survivors; mladý dospělý; Betacoronavirus; dítě; ženské pohlaví; mladiství; Cancer Survivors; Female; předškolní dítě; virová pneumonie